The Political Economy of European Wine Regulations*. (10th January 2014) - Meloni, Giulia; Swinnen, Johan
Abstract The wine market in the European Union is heavily regulated. Despite the many distortions in the wine market as a consequence, reforming the regulations has proven difficult. This paper analyzes the political economy mechanism that created existing wine regulations. We document the historical origins of the regulations and relate these to political pressures that resulted from international integration, technological innovations, and economic developments. (JEL Classifications: K23, L51, N44, N54, Q13)